Trans-Resveratrol Oral Bioavailability in Humans Using LipiSperse™ Dispersion Technology - David Briskey; Amanda Rao (MDPI AG, 2020)
Resveratrol is a naturally produced compound that has been well researched for its potential health benefits. The primary hindrance towards resveratrol's therapeutic efficacy is its traditionally poor oral bioavailability. LipiSperse® is a novel delivery system designed to increase the dispersion of lipophilic ingredients, like resveratrol, in aqueous environments. This single-dose, double-blind, randomized study compared the pharmacokinetics of a commercially available resveratrol with (Veri-Sperse®) and without (Veri-te) the LipiSperse® delivery complex. Healthy adults randomly received a single dose of either 150 Veri-te, 75 Veri-Sperse®, or 150 mg Veri-Sperse®. Venous blood samples were taken prior to dosing in a fasted state and at 0.5, 1, 2, 3, 4, 5, 6, 8 and 24 h post supplementation. Plasma trans-resveratrol conjugates were measured by liquid-chromatography tandem mass spectrometry (LC-MS/MS). The area under the curve (AUC) (0-24 h), maximum concentration (Cmax), and time of maximum concentration (Tmax) of plasma conjugates were calculated. The 150 mg dose of Veri-Sperse® had a 2-fold increase in absorption (AUC) and a 3-fold increase in Cmax of trans-resveratrol conjugates compared to 150 mg Veri-te. There was no statistical difference between 75 Veri-Sperse and 150 mg Veri-te for AUC or Cmax of resveratrol conjugates. These findings provide support for the use of LipiSperse® to improve absorption of resveratrol.